Apparatus methods for monitoring dental treatment of patients with cervicobrachyalgia - A. V. Mitronin; A. V. Boldin; T. S. Zaushnikova; Yu. L. Kudryavtsev; M. I. Mitereva (LLC "Endo Press", 2021)
Relevance. Pain localized in the anatomical areas adjacent to the temporomandibular joint is an actual problem for doctors of various specialties.Aim. To develop a diagnostic algorithm and a comprehensive program for the treatment of patients with cervicobrachialgia combined with pathological dental occlusion.Materials and methods. The study involved 90 people of both sexes aged 18 to 55 years; they were divided into 3 clinical study groups (25 people each) and 1 control group (15 healthy individuals). The comparison was carried out depending on the chosen treatment tactics: manual therapy was used in group 1, dental treatment was performed in group 2, a combination of manual therapy and dental rehabilitation with correction of occlusal relationships of the jaws was in group 3.Results. All patients were prescribed pharmacotherapy with NSAIDs to relieve myofascial pain at the level of the muscles of the neck and shoulder girdle. As a result of the study, the most effective algorithm for diagnosis and complex treatment of patients with cervicobrachialgia was identified.Conclusions. Namely, statistically significant positive results were observed in patients of group 3, where manual therapy, pharmacotherapy and complex dental treatment was conducted. In "difficult" patients it is advisable to carry out 3D X-ray visualization, computer functional methods for studying the maxillofacial area and adjacent areas to identify the cause and interrelationships of the patient's disease.